An Analysis Of Differences In Earnings Management Among Property Companies Listed On The Indonesia Stock Exchange Before And After The Adoption Of PSAK 72 (2018-2021) - Muhammad Ridwan Nur Islami; Juanda Astarani; Rusliyawati Rusliyawati (Universitas Ibn Khladun Bogor, 2026)
This study compares the level of accrual-based earnings management among property firms listed on the Indonesia Stock Exchange before and after the implementation of PSAK 72, covering 2018–2021. Using a comparative and associative quantitative approach, the study analyzes 26 property companies (104 financial statements) selected via purposive sampling. Earnings management is measured through discretionary accruals (DA) based on the Modified Jones Model, winsorized at the 1st and 99th percentiles to mitigate extreme values caused by the COVID-19 pandemic, and tested using the Wilcoxon Signed Rank Test and panel data regression. Results show no significant difference in DA before (mean = -0.00099) and after (mean = 0.00077) PSAK 72 implementation (W=130, p=0.258). Panel regression using the Random Effects model (selected via the Hausman Test) similarly indicates no significant effect of PSAK 72 on DA (β=0.0107, p=0.3414). Among control variables, only ROA significantly affects DA (β=0.2086, p=0.0056), though positively—contrary to the initial hypothesis—while Leverage, Firm Size, and Sales Growth show no significant effect. The model explains only 7.28% of DA variation (corr(y,ŷ)²=0.0728). These findings suggest that PSAK 72's impact on earnings management, if any, is likely masked by the severe economic shock of COVID-19, which coincided with the standard's implementation period.